Proteomic Response to Environmental Stresses in the Stolon of a Highly Invasive Fouling Ascidian - Li, Xi; Li, Shiguo; Cheng, Jiawei; Fu, Ruiying; Zhan, Aibin (Frontiers in Marine Science, 2021)
Ascidians, particularly those highly invasive ones, are typical fouling organisms to cause significantly negative ecological and economic influence in coastal ecosystems. Stolon, which is the unique structure of some solitary ascidians to complete the essential process of adhesion, possesses extremely high tolerance to environmental stresses during biofouling and invasions. However, the mechanisms underlying environmental tolerance remain largely unknown. Here, we used the quantitative proteomics technology, isobaric tags for relative and absolute quantitation (iTRAQ), to investigate the molecular response to environmental challenges (temperature and salinity) in the stolon of a highly invasive fouling ascidian, Ciona robusta. When compared with the control, a total of 75, 86, 123, and 83 differential abundance proteins were identified under low salinity, high salinity, low temperature, and high temperature stress, respectively. Bioinformatic analyses uncovered the key pathways under both temperature and salinity stresses, including “cytoskeleton,” “signal transduction,” and “posttranslational modification,” which were involved in stolon structure stability, protein synthesis, and stress response activation. Under the low salinity stress, the “extracellular matrix” pathway was identified to play a crucial role by regulating cell signal transduction and protein synthesis. To deal with the high salinity stress, stolon could store more energy by activating “carbohydrate/lipid transport” and “catabolism” pathways. The energy generated by “lipid metabolism” pathway might be beneficial to resist the low temperature stress. The upregulation of “cell cycle” pathway could inhibit cell growth, thus helping stolon conserve more energy against the high temperature stress. Our results here provide valuable references of candidate pathways and associated genes for studying mechanisms of harsh environmental adaptation and developing antifouling strategies in marine and coastal ecosystems.